The Effect of Partial Substitution of Ge-S-Cd Alloys on the Density of Energy States - Zainab Abd Al-hadi; Kareem Ali Jasim (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2024)
Five samples of the ternary alloy Ge-S-Cd were created using the melting point method, and the effects of partially substituting cadmium for germanium were determined. and partial substitution of germanium by cadmium was used to study the change in electrical conductivity. Electrical experiments were performed on Ge35-xS65Cdxternary alloy with x = 0, 5, 10, 15, and 20. It was discovered that the conductivity (σdc) rises with rising temperature in all samples under experiment. This confirms that the samples have semiconductor behavior. It has been observed that there are three regions of electrical conductivity in the electrical conductivity curve at low, moderate, and high temperatures. The preexponential elements and effective energies of each of the three conduction regions were calculated for each of the Cadmium values. It was found that all of them were impacted by a rise in the value of cadmium in the ingot. A numerical analysis of the conductivity equation was also performed to calculate the energy of the expanding states' density in local states and at the Fermi level. It has been observed that all of the values of samples change with the rising value of cadmium concentration.